The Effect of Product Differentiation, Customer Experience and Product Quality on The Purchase Decision of Compass Shoes in Jakarta - Deni Akbar Saputro; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
The purpose of this study was to determine and analyze the effect of Product Differentiation, Customer Experience and Product Quality on purchasing decisions for Compass shoes in Jakarta and also to identify and analyze the most dominant factors influencing purchasing decisions. This research was conducted on respondents in the Jakarta area. The population in this study were members of the Teman Compass Official (TCO) who were still active and users of Compass shoes. The sample of this study was 98 respondents obtained by purposive sampling method. The analytical method used is descriptive analysis method and multiple linear regression analysis method. The type of data used is primary data and secondary data obtained through the study of documentation and a list of questionnaire questions whose measurements are using a Likert scale. The data was statistically processed using the IBM SPSS statistics 23 program by testing the F-test model, t-test, and the determinant coefficient (????2). The results of this study indicate that simultaneously product differentiation, customer experience and product quality have a positive and significant impact on purchasing decisions for Compass shoes in Jakarta. Partially, each variable product differentiation, customer experience and product quality has a positive and significant effect on purchasing decisions. Then product differentiation is the most dominant variable influencing the decision to purchase Compass shoes in Jakarta. Furthermore, the value of R Square is 0.395, which means that the variability of the dependent variable which can be explained by the independent variables, namely product differentiation, customer experience and product quality, is 39.5%, while the remaining 60.5% can be explained by variables not examined in this study.